1993
DOI: 10.1038/363536a0
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and sequencing of DNA from a 120–135-million-year-old weevil

Abstract: DNA has been successfully isolated from both fossilized plant and animal tissues. The oldest material, dated as 25-40 million years old (Tertiary), was obtained from amber-entombed bees and termites. Tissues from both these insects yielded DNA of good quality, which could be amplified by the polymerase chain reaction (PCR) and subsequently sequenced, including the genes encoding 18S ribosomal RNA and 16S rRNA. We report here the extraction of DNA from a 120-135-million-year-old weevil (Nemonychidae, Coleoptera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(85 citation statements)
references
References 10 publications
0
81
0
3
Order By: Relevance
“…In contrast to materials fossilized for millions of years (Cano et al 1993;DeSalle et al 1992;Golenberg et al 1990;Woodward et al 1994), subfossils of lesser age (Cooper 1994;Handt et al 1994;Nielsen et al 1994;Higuchi et al 1984;Pääbo 1985;Pääbo et al 1989;Ubaldi et al 1996, Willerslev et al 1999, such as lichens exposed by presentday ablation of glaciers, may yield DNA sequences of sufficient quality and quantity to permit highly resolved phylogenetic analyses. Subfossil lichens have been observed in a 2-to 5-m broad zone at several sites along the ablating margins of Greenland's ice cap (Alstrup 1995;Alstrup 1997a, 1997b;Fahselt et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to materials fossilized for millions of years (Cano et al 1993;DeSalle et al 1992;Golenberg et al 1990;Woodward et al 1994), subfossils of lesser age (Cooper 1994;Handt et al 1994;Nielsen et al 1994;Higuchi et al 1984;Pääbo 1985;Pääbo et al 1989;Ubaldi et al 1996, Willerslev et al 1999, such as lichens exposed by presentday ablation of glaciers, may yield DNA sequences of sufficient quality and quantity to permit highly resolved phylogenetic analyses. Subfossil lichens have been observed in a 2-to 5-m broad zone at several sites along the ablating margins of Greenland's ice cap (Alstrup 1995;Alstrup 1997a, 1997b;Fahselt et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of non-racemized amino acids in insect tissues from ambers of various ages suggested that anhydrous conditions within the amber promoted long-term preservation (Bada et al 1994;Wang et al 1995). There have been seven reports to date of DNA retrieval from fossil insects and plants in amber (Higuchi & Wilson 1984;Cano et al 1992Cano et al , 1993DeSalle et al 1992;De Salle 1994;Henwood 1992;Poinar et al 1993). In addition, there have been claims of viable bacteria from the guts of stingless bees in amber (Cano & Borucki 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The association of the same or similar basidiomycetous and ascomycetous saprobes with ancient ascolichens, polar icecap cores, and grass clothing of the Tyrolean Iceman suggests that these fungi may be common contaminants of historical and prehistorical ice-preserved materials. Therefore, the molecular characterization of these saprobic fungi will be crucial to future studies of DNA and other constituents of subfossil and fossil tissues (Cano et al 1993;DeSalle et al 1992;Golenberg et al 1990;Woodward et al 1994). Although improved laboratory techniques may eventually reduce or eliminate contamination by modern DNAs of laboratory and human origin, it is only by understanding the ecology and genetic characteristics of modern microbes that we can document and authenticate ancient DNA.…”
Section: Resultsmentioning
confidence: 99%